Pendidik Yang Membelajarkan (Gaya Bank vs Hadap Masalah) - Samsul Bahri (Institut Agama Islam Negeri Palopo, 2019)
This paper proves that the fundamental problem in teaching is the instructor who uses a bank style teaching model that casts off the potential of student creativity which leads to authoritarian feudalistic teaching in which students such as tabula rasa, blank white paper must be filled, therefore the facts empirically, the battle between the two models of teaching is still very much dominated by the teaching model in the style of the bank. By that, the writing of giving agat solutions to teaching models to problems is the choice of the instructors because this model is able to build participants' creativity and democratization in learning. With this model education can develop a humanizing mission for human beings, or students and able to produce generations that are of good quality in a scientific way, as well as morals seem to be realized.